Missing Matthew's Political Messiah: A Closer Look at His Birth and Infancy Narratives - Baxter, Wayne (Bulletin for biblical research, 2017)
Many Christians often assume that when Matthew informs his audience that Jesus “will save his people from their sins,” the saving the Evangelist has in mind is “spiritual,” namely, the forgiveness of sins. This article contends that when Matt 1:21 is examined in its narrative and social-historical contexts, it becomes clear that Matthew envisioned a messiah who would also save his people from the political ramifications of their sins.